Wellness Program on Weight Loss, Fasting Blood Sugar and Cholesterol Levels in Workers - Artanto, Ardi; badri, putri rizki; Fitrianti, Yuni; Isnada, Muhammad Dimas; Meisananda, Nefa Hulwa (Faculty of Medicine, 2024)
The wellness program is a health program that can be used to prevent non-communicable diseases in company workers. Obesity and high blood sugar can be predictors of diabetes mellitus. High cholesterol levels in workers can cause other complications such as heart disease or even stroke which can reduce performance.The aim of this study was to assess changes in body weight, fasting blood sugar levels, and cholesterol before and after the wellness program. In this study, the sample used was workers at PT Pertamina Refinery Unit III Plaju who had taken part in a wellness program. The research period took place from January to July 2023. Sample collection used a total sampling technique with a retrospective cohort design. Body weight, fasting blood sugar and cholesterol levels were measured on workers before and after implementing the wellness program. After data collection was carried out, the bivariate data was analyzed using the Wilcoxon test with the SPSS program. This study found that there was a significant difference between body weight with a p-value of 0.000 and a p-value of 0.000 for cholesterol levels before and after the wellness program. There was no significant difference between fasting blood sugar levels before and after the wellness program with a p-value of 0.783. Wellness programs can reduce body weight and cholesterol levels in workers.